2013
DOI: 10.3109/17549507.2013.796000
|View full text |Cite
|
Sign up to set email alerts
|

The use of a standardized language assessment tool to measure the language development of urban Aboriginal preschoolers

Abstract: The use of standardized language assessment tools with Australian Indigenous children has been criticized for language and cultural reasons; however, this has not been tested in an urban context. The aim of the study was to explore the language performance of a small sample of urban Aboriginal preschoolers on a standardized language tool compared with a conversational sample. Fifteen participants (drawn from a birth cohort study of over 150 Aboriginal infants born at a metropolitan hospital) completed the Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…Notably, this cohort is all English speaking with no other reported languages by the families. As shown in a previous study on the Gudaga cohort (Miller, Webster, Knight, & Comino, ), some Aboriginal English may be present, but this was not reported by the families as a different language.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, this cohort is all English speaking with no other reported languages by the families. As shown in a previous study on the Gudaga cohort (Miller, Webster, Knight, & Comino, ), some Aboriginal English may be present, but this was not reported by the families as a different language.…”
Section: Methodsmentioning
confidence: 99%
“…Combined, these studies included a total of 438 Aboriginal and Torres Strait Islander children assessed between 3 and 13 years, 8 months of age, though it appears 2 studies 4,47 included the same 19 children as participants. Of the 9 included studies, 3 took place in the urban centre of Campbelltown, New South Wales, 23,48,49 which is classified as a major city in Australia 50 . Another study was identified as taking place in an urban area of North Queensland.…”
Section: Participants and Study Locationsmentioning
confidence: 99%
“…The aims of the 9 studies varied widely. Five of the 9 studies were aimed at describing the language abilities of Aboriginal and Torres Strait Islander children; 4,47,48,52,53,55 3 of these compared results of standardised and non-standardised assessments. 4,47,48,52,53,55 while a fourth included analysis of AE features in the language sample attained as part of the standardised assessment.…”
Section: Aims Of Included Studiesmentioning
confidence: 99%
“…Both the findings reported in this paper and limitations discussed above highlight the need to continue investigation into strategies to support vulnerable children's language learning. While not the focus of this paper, recent research studies have focused on the complexity of Aboriginal children's language environments (McLeod, Verdon & Bennetts Kneebone, 2014), the development of Australian Aboriginal children's language (Farrant, Shepherd, Walker & Pearson, 2014;Vaughan, Wigglesworth, Loakes, Disbray & Moses, 2015), and the need to use assessments of language that are appropriate to English as additional language learners for an accurate representation of children's language abilities (Gould, 2008;Miller, Webster, Knight & Comino, 2014;Pearce & Williams, 2013). These studies highlight the paucity of research on Aboriginal children's language acquisition and the high incidences of diagnosed language delay prevalent within Aboriginal populations.…”
Section: Future Directionsmentioning
confidence: 99%